THE IMPACT OF COMPETITIVE STRATEGIES, AND STRATEGIC HUMAN RESOURCE MANAGEMENT ON FIRM PERFORMANCE OF PALESTINE - Sayyad, Nermeen (Archives of Business Research, 2017)
This paper examines the impact of competitive strategies and strategic Human Resource Management on Firm Performance of Palestine from various critical perspectives. Rapid environmental changes, competition to provide innovative products and services, changing customer and investor demands and globalization have become the standard backdrop for firms. Sustained competitive advantage could be generated from a firm’s human capital by designing strategic human resource management to diagnose a firm’s strategic needs which is required to implement a competitive strategy and achieve operational goals. Effective human resource management strategy systematically organizes all individual human resource management measures to directly influence employee attitude and behavior in a way that leads business to achieve its competitive strategy. The researcher has selected corporate and non-corporate firms as well as small and Medium Corporation were chosen in different areas of Palestine (south, north, and middle) 106 respondents selected from 45 firms across the three zones of Palestine. The general objective of the study is to investigate the place of Strategic Human Resource Management in improving corporate performance among mentioned firms in Palestine. The study used descriptive statistics (frequencies, means and percentages) to answer the three research questions posed for the study. The Spearman Rank Correlation Coefficient was used to test the three hypotheses that guided the study. The final results showed that there is a strong positive correlation between strategic HRM and performance level of competition in the firms. It was also concluded that SHRM is an important and indispensable tool for any organizations performance and for any organization that wants to gain competitive advantage over others. Finally, this article develops a conceptual framework that explains the relationship between strategic human resource management, competitive strategies and firm Performance.